# Algebra II

1)What method(s) would you choose to solve the equation:

x2 + 2x - 6 = 0

A. Square roots; there is no x-term.

B. Quadratic formula, graphing; the equation cannot be factored easily since the numbers are large.

C. Factoring; the equation is easily factored.

D. Quadratic formula, completing the square or graphing; the coefficient of x2-term is 1, but the equation cannot be factored. <<<------

2)What are the solutions of the equation?
c^2 - 10c = 0

A. 1, – squareroot10 <<<----

B. 0, –10

C. 0, sqrt10

D. 0, 10

3)Use the discriminant to determine the number of real-number solutions for the equation:
8x2 + 8x + 2 = 0

A. one solution <<<---

B. two solutions

C. no solutions

D. infinitely many solutions

4)What are the solutions of the equation: z2 - 12z + 36 = 0?

A. -6, 6 <<----

B. 6, 6

C. 6, -6

D. -6, -6

thank u!

1. 👍 0
2. 👎 0
3. 👁 279
1. 1. I would choose B.

2. c^2 - 10c = c(c-10) = 0
Now what do you think?

4. z^2 - 12z + 36 = (z-6)(z-6) = 0
Now what do you think?

3. Since it seems like you are just guessing, I did not bother to answer.

1. 👍 0
2. 👎 0
posted by PsyDAG

## Similar Questions

1. ### algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x + y = 2 3x + 2y = 9

asked by mel on August 16, 2012
2. ### Algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x – 2y = 2 x + 3y = 17

asked by Mike on April 25, 2011
3. ### How do I do this.?(Math.)

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second

asked by Margie on February 5, 2007
4. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

asked by Svetlana on October 17, 2006
5. ### ALGEBRA 1!PLZ HELP!

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

asked by SANDRO! on November 6, 2006
6. ### math,algebra II

I need someone to explain to me step by step the process of this problem its in my book as an example but i am not understanding it. Ive researched the explanation of the ECHELON METHOD...BUt i am not seeingit...this is the

asked by alma20 on June 1, 2007
7. ### Math

PLEASE CHACK MY ANSWER!!! Discussion for Applications of Linear Systems When solving a system of equations, how do you determine which method to use? My answer: I determine which method to use by looking at the equations. If both

asked by Matthew on December 15, 2016
8. ### Factoring

What does 3x^3-3x+2=0 come out to? How would I solve this? Is the x cubed supposed to be x squared? You can compare the equation with the identity: (a+b)^3 = a^3 + 3 a^2 b + 3 a b^2 + b^3 which you can rewrite as: (a + b)^3 = 3 ab

asked by Ace on May 30, 2007
9. ### maths

1.solve the set of linear equation by matrix method.a+3b+2c=3,2a-b-3c=-8,5a+2b+c=9 solve for a,b,c 2.solve by Guassian elimination method, (a)a+2b+3c=5,3a-b+2c=8,4a-6b-4c=-2, (b)

asked by emmanuel konwei on March 3, 2015
10. ### Algebra II

If you were to use the substitution method to solve the following system, choose the new system of equations that would result if x was isolated in the third equation. 2x - 3y + z = -4 2x - 2y + z = -1 x - 2y + 3z = -6 5x + 7y = 6

asked by Asianthatsuxatmath on January 17, 2014
11. ### math ALGEBRA

Solve by either the substitution method or the addition or subtraction method 2m=n-3 3m=2n-9 Just replace n with (2m + 3) in the second equation. Then solve for m. Once you know the value of m, use either of your equations, such

asked by DANIELLE on December 21, 2006

More Similar Questions